2000
DOI: 10.1037/1076-898x.6.2.104
|View full text |Cite
|
Sign up to set email alerts
|

The dynamics of trust: Comparing humans to automation.

Abstract: Complex industrial environments involve cooperation between operators and automation. The strategies used to allocate tasks to automation are a crucial component of that cooperation and are known to be affected by the operators' trust in the automation. In 2 simulated process control experiments, the authors compared trust in automation with trust in human partners in equivalent situations. Experiment 1 found the relationship between trust and task allocation to be qualitatively identical, but quantitatively a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
111
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(121 citation statements)
references
References 17 publications
(56 reference statements)
9
111
1
Order By: Relevance
“…However, drivers also relied on the ACC more during the first half of the rain/ traffic periods than during the second half. This nonlinear reliance across time shows that reliance does not recover as quickly as reliability, a finding consistent with that of other researchers (Lee and Moray, 1994;Lewandowsky et al, 2000;Lee and See, 2004). Reliance results for failure and non-failure periods together provide a high-level representation of how often drivers use the ACC and in what operating condition: normal or failure.…”
Section: Automation Reliancesupporting
confidence: 71%
“…However, drivers also relied on the ACC more during the first half of the rain/ traffic periods than during the second half. This nonlinear reliance across time shows that reliance does not recover as quickly as reliability, a finding consistent with that of other researchers (Lee and Moray, 1994;Lewandowsky et al, 2000;Lee and See, 2004). Reliance results for failure and non-failure periods together provide a high-level representation of how often drivers use the ACC and in what operating condition: normal or failure.…”
Section: Automation Reliancesupporting
confidence: 71%
“…On the contrary, if operators are more confident in their own abilities than they trust the automation, then they will likely choose manual control. Empirical evidence for this was found in a number of studies (e.g., De Vries, Midden, & Bouwhuis, 2003;Lee & Moray, 1992, 1994Lewandowsky, Mundy, & Tan, 2000). Riley's model also accounts -although not very detailed -for the influence of operator states (fatigue) on reliance and the time dynamics influencing the relation between trust and reliance.…”
Section: Theoretical Approaches To Reliance On Automationmentioning
confidence: 88%
“…Whereas Muir and Moray (1996) found that operators' trust was a very good predictor of their reliance, others (De Vries et al, 2003;Lee & Moray, 1992, 1994Lewandowsky et al, 2000) found that operators' reliance could be more appropriately predicted by the relationship between their trust in the automation and their self-confidence in manually controlling the system. Specifically, Lee and Moray (1994) found that participants' reliance could be predicted by a logit function of the difference between trust and self-confidence, whereby in general operators tend to rely more on automation when their trust in the automation exceeds their self-confidence, and tend to engage in manual control when trust was lower than their self-confidence.…”
Section: The Influence Of Automation Reliability On Trust and Reliancementioning
confidence: 99%
See 1 more Smart Citation
“…The social-psychological component is captured in the intended behaviour being situated within a set of socially defined norms governing whether a behaviour is normal/acceptable (Lewandowsky, Mundy & Tan, 2000). Finally, and importantly for trust, is the emotional/affective component captured under the various attitudes the driver has about the behaviour (Merritt et al, 2013).…”
Section: Introductionmentioning
confidence: 99%